Harnessing the Immunogenic Potential of Gold Nanoparticle-Based Platforms as a Therapeutic Strategy in Breast Cancer Immunotherapy: A Mini Review - Chen, Xiao-Yang; Yung, Lin-Yue Lanry; Tan, Puay Hoon; Bay, Boon Huat (Frontiers in Immunology, 2022)
Breast cancer remains the most common malignancy among women worldwide. Although the implementation of mammography has dramatically increased the early detection rate, conventional treatments like chemotherapy, radiation therapy and surgery, have significantly improved the prognosis for breast cancer patients. However, about a third of treated breast cancer patients are known to suffer from disease recurrences and progression to metastasis. Immunotherapy has recently gained traction due to its ability to establish long-term immune surveillance, and response for the prevention of disease recurrence and extension of patient survival. Current research findings have revealed that gold nanoparticles can enhance the safety and efficacy of cancer immunotherapy, through their unique intrinsic properties of good biocompatibility, durability, convenient surface modification, as well as enhanced permeability and retention effect. Gold nanoparticles are also able to induce innate immune responses through the process of immunogenic cell death, which can lead to the establishment of lasting adaptive immunity. As such gold nanoparticles are considered as good candidates for next generation immunotherapeutic strategies. This mini review gives an overview of gold nanoparticles and their potential applications in breast cancer immunotherapeutic strategies.